Manajemen Kinerja Kelembagaan Dalam Meningkatkan Kualitas Air Bersih Pada Perusahaan Daerah Air Minum - Andri Pratama Saputra; Mohamad Ichsana Nur (Jurusan Administrasi Publik FISIP UIN SGD Bandung, 2019)
Performance management issues in the local water companies, which is called PDAM, in Indonesia are often encountered such as slow service in serving public needs and complaints. In 2013, the performance of PDAMS was categorized as unhealthy with a total performance value of 2.50 (ranging from 2.2 to 2.8). This research aims to analyze performance evaluations of Badan Pendukung Pengembangan Sistem Penyediaan Air Minum as a performance appraisal body of PDAM and what kind of factors influencing the performance through the PDAM performance assessment technical guidelines. The approach used in this paper is quantitative with descriptive research. The data collection of this research is a literature study. The results show that the greater the NRW level and the employee ratio, the worse the PDAM performance. For other indicators identified as having positive causality because of the greater the value, the better the performance value.